Strategic guidelines for supply chain coordination in healthcare and a mathematical model as a proposed mechanism for the measurement of coordination effects (2016)
Supply chain (SC) management implies a large number of interactions and a great deal of cooperation between the organizations that make up the supply chain in order to fulfill the purposes of logistics processes such as supply, distribution and warehousing. Much research has been carried out to illustrate the advantages of coordinating these processes at different stages of supply chain planning. However, these studies appear to be separate efforts. This study proposes methodological guidelines for the coordinated planning of the supply chain in the context of the healthcare services, considering the global benefits to its members by using primary information collected at several health service institutions. The proposal also includes a mixed-integer programming model to show how organizational coordination contributes to a reduction of the overall costs throughout the chain.